Human herpesvirus 8 and Kaposi sarcoma: how should we screen and manage the transplant recipient?. Issue 6 (22nd December 2021) - Mikulska, Malgorzata; Balletto, Elisa; Mularoni, Alessandra
Abstract : Purpose of review: HHV-8-associated diseases are rare but potentially fatal in transplant recipients. Important differences exist in the distribution of HHV-8 seroprevalence, which might contribute to the lack of uniform approach to HHV-8. The aim of this review was to discuss recent updates in screening and management of HHV-8 after transplant. Recent findings: Increasing attention has been given to the nonmalignant but potentially fatal inflammatory syndrome caused by HHV-8 in solid organ transplant (SOT) recipients. At-risk groups include HHV-8-IgG D+/R- transplant and HHV-8-positive recipients. Severe cases of donor-derived HHV-8 disease, mainly Kaposi sarcoma, frequently without skin involvement and some diagnosed at autopsy, highlight the need to increase clinicians' awareness, to implement effective preemptive strategies and to perform rapid diagnosis. In HSCT setting, HHV-8-associated disorders are very rare. Summary: Identification of SOT recipients at risk through reliable serology is warranted and the utility of preemptive management and HHV-8-DNA monitoring should be studied. Clinicians should be aware of severe nonmalignant disorders and of early post-SOT Kaposi sarcoma cases with lymph node or transplanted organ involvement in order to provide prompt diagnosis and treatment. No screening for HHV-8 is warranted after HSCT but rapid diagnosis and reduction of immunosuppression remain fundamental.